Shifting attitudes toward suicide over time: A latent profile analysis using the Korea National Suicide Survey - Lee, Hyunju; Rhee, Sang Jin; Kim, Min Ji; Park, Christopher Hyung Keun; Yang, Jeong Hun; Son, Kyunghoon; Park, Jong-Ik; Ahn, Yong Min (Frontiers in Psychiatry, 2023)
South Korea has a high suicide rate, and changes in sociodemographic factors can further increase the rate. This study aims to (1) classify participants using the Attitudes toward Suicide Scale (ATTS) through latent profile analysis (LPA), (2) identify and compare the associations between sociodemographic factors with the ATTS in two survey years (2013, 2018), and (3) determine the moderating effect of survey year. Six sub-factors of the ATTS were used for LPA with a total of 2,973 participants. Sociodemographic characteristics were compared between groups, and multinomial logistic regression was conducted for each survey year. A moderation analysis was conducted with the survey year as moderator. LPA identified three groups of attitudes toward suicide: incomprehensible (10.3%), mixed (52.8%), and permissive (36.9%). The proportion of permissive attitudes increased from 2013 (32.3%) to 2018 (41.7%). Participants reporting suicidal behavior were more likely to be in the mixed and permissive groups than the incomprehensible group in both years. People reporting no religious beliefs were associated with the permissive group in the two survey years. The influence of education and income levels on groups differed by survey year. There were also significant changes between 2013 and 2018 in attitudes toward suicide in the Korean population.